Analisis BMC Usaha Jambu Kristal di Desa Suci Kecamatan Panti Kabupaten Jember - Hijriyah, Hilmi Hafifatul; Lutfiah, Hikmatul (KUBIS, 2023)
The Business Model Canvas (BMC) is a strategic management tool for quickly and easily defining and communicating a business idea or concept. The research objectives were (1) to find out the Business Model Canvas (BMC) for the crystal guava business in Suci Village, Panti District (2) to find out the SWOT analysis for the crystal guava business in Suci Village, Panti District. The research method is to use descriptive analysis, and data analysis by observation, interviews and questionnaires. The results of this study indicate that the harvest is in demand by all groups ranging from children, adults and the elderly. Because it tastes sweet, crunchy and the price is cheap compared to other crystal guava sellers. The results of the SWOT analysis are increasing increasing capital, increasing production and innovating products derived from crystal guava and increasing marketing with good consumer perception so that it can be increased more intensely by promoting it to new consumers.